Bumps and humps in the success of Tirzepatide as the first GLP1 and GIP receptor agonist - Rouchan Ali; Sharma Arvind Virendra; Pooja A Chawla (Health Sciences Review, 2022)
Glucagon-like peptide 1 (GLP-1) receptor agonists have acquired importance in Type 2 diabetes (T2D) treatment due to their glycemic advantages, cardiorenal effects, and favorable body weight. Despite this, the continuous discovery of higher effectiveness treatments is critical to addressing ongoing difficulties in the accomplishment of metabolic targets in many T2D patients. Tirzepatide is a unimolecular dual GLP-1 and Glucose-dependent insulinotropic polypeptide (GIP) receptor agonist that is being developed for the treatment of T2D. Tirzepatide was approved in May 13, 2022 by the United State Food and Drug Administration (USFDA) with the brand name Mounjaro as the first and the only GLP-1 and GIP receptor agonist to treat T2D. This review outlines essential features of tirzepatide including chemistry, synthesis, pharmacology and mechanism of action of tirzepatide as well as pharmacodynamics, pharmacokinetic and reported clinical trials.